2014
DOI: 10.7166/25-1-739
|View full text |Cite
|
Sign up to set email alerts
|

The Role Of Supervisor Support In Predicting Employee Job Satisfaction From Their Perception Of The Performance Management System: A Test Of Competing Models In Engineering Environments

Abstract: Past studies of performance management systems (PMS) have focused more on designing the framework and less on the effect it has on employees. Moreover, employees in developing countries may not be knowledgeable or familiar with PMS. This paper proposes two competing statistical models to examine the roles that supervisor support (SS) has in engineering organisations. It was found that SS is a mediator, but not a moderator, in the relationship between PMS and employee job satisfaction. In other words, SS partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 29 publications
(34 reference statements)
3
26
0
Order By: Relevance
“…Other studies found that individuals who receive high levels of supervisor support cope better with stress and are more satisfied with their jobs (Erturk, 2014;Ghapanchi & Aurum, 2011). While some studies suggest that supervisor support acts as a buffer that moderates the relationship between role stressors and job satisfaction, other studies have failed to replicate these results (Baloyi, Van Waveren & Chan, 2014). As indicated in Figure 1, supervisor support may also play a role by linking role stress to job satisfaction.…”
Section: Hypothesesmentioning
confidence: 57%
See 2 more Smart Citations
“…Other studies found that individuals who receive high levels of supervisor support cope better with stress and are more satisfied with their jobs (Erturk, 2014;Ghapanchi & Aurum, 2011). While some studies suggest that supervisor support acts as a buffer that moderates the relationship between role stressors and job satisfaction, other studies have failed to replicate these results (Baloyi, Van Waveren & Chan, 2014). As indicated in Figure 1, supervisor support may also play a role by linking role stress to job satisfaction.…”
Section: Hypothesesmentioning
confidence: 57%
“…In other words, supervisor support may intervene between role stress and job satisfaction by attenuating or preventing negative role stress outcomes such as a reduction in job satisfaction. Similarly, results are equally conflicting regarding the possibility of supervisor support mediating the relationship between role stressors and job satisfaction (Baloyi et al, 2014). This study strives to clarify these results by verifying the possibility of the quality of supervisor support probably moderating and/or mediating the association between role stressors (role conflict and ambiguity) and job satisfaction.…”
Section: Hypothesesmentioning
confidence: 82%
See 1 more Smart Citation
“…One of the variables with which supervisor support is positively associated is job satisfaction (Babin and Boles, 1996;Baloyil et al, 2014;Demirhan et al, 2014;Griffin et al, 2001;Ng and Sorenson, 2008). Job satisfaction refers to the happiness, pleasure, or satisfaction that employees take from their work.…”
Section: Introductionmentioning
confidence: 99%
“…Employees are found to be satisfy with their work when there is a high level of supervisor support in a workplace (Baloyi, Van Waveren and Chan, 2014).…”
Section: Journal Of Management Researchmentioning
confidence: 99%